2021
DOI: 10.1002/brb3.2046
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress induced depressive‐like behavior and region dependently high CRP level in offspring rats

Abstract: Introduction To explore the changes in C‐reactive protein (CRP) level in different regions of one old offspring rats exposed to prenatal stress (PS). Methods The rat model was constructed with prenatal restraint stress on pregnant dams on days 14–20 of gestation. Offspring rats were randomly divided into PS susceptibility (PS‐S) group and control (CON) group. Behavioral experiments including sucrose preference test (SPT), open‐field test (OFT), and forced swimming test (FST) were used to measure depressive‐lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
3
1
0
Order By: Relevance
“…Moreover, in the EPM, pups born to prenatally stressed dams exhibited increased entries into the closed arms. Taken together, these findings suggest that PS induced anxiety-like behaviour and impairments in locomotor activity of offspring, which is in line with several previous studies indicating that exposure to chronic stress in the developmental period is linked to anxiety and depression (Dong et al, 2018;Gur et al, 2017;Li et al, 2021). Excitingly, pretreatment of pregnant dams with agmatine before the induction of PS resulted in improved locomotor activity and attenuated the anxiety-like behaviour in the female offspring, which implies that prenatal administration of agmatine could be a preventive measure against PS-associated depression and anxiety.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, in the EPM, pups born to prenatally stressed dams exhibited increased entries into the closed arms. Taken together, these findings suggest that PS induced anxiety-like behaviour and impairments in locomotor activity of offspring, which is in line with several previous studies indicating that exposure to chronic stress in the developmental period is linked to anxiety and depression (Dong et al, 2018;Gur et al, 2017;Li et al, 2021). Excitingly, pretreatment of pregnant dams with agmatine before the induction of PS resulted in improved locomotor activity and attenuated the anxiety-like behaviour in the female offspring, which implies that prenatal administration of agmatine could be a preventive measure against PS-associated depression and anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…It is well‐established that PS has a wide range of potential impacts on a developing foetus, including structural alterations, which could underlie adverse cognitive and behavioural outcomes during the postnatal period (Charil et al, 2010; Lautarescu et al, 2020). Numerous studies have suggested that PS is associated with increased depressive‐like behaviour (Fatima et al, 2017; Li et al, 2021), anxiety (Gur et al, 2017; Miyagawa et al, 2011) and addictive tendencies (Stratilov et al, 2020) in the offspring. As PS confers a later life vulnerability of offspring to negative behavioural outcomes, it is important to uncover the underlying neural mechanisms of PS‐associated outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Male pups seemed to be more susceptible to these effects. Our findings showed that rats and their offspring stressed during pregnancy in open‐field testing exhibited significantly reduced exploratory behavior and increased anxiety‐like behavior, consistent with previous studies (Li et al, 2021; Zhang et al, 2019). Prenatal stress was associated with anhedonia (represented by decreased sucrose preference rates in SPT), behavioral despair and helplessness.…”
Section: Discussionsupporting
confidence: 92%
“…Animals exposed to PNS showed significant behavioral differences that resemble specific psychopathologic domains, with reduced sociability, increased anxiety and anhedonic behavior. These data are in line with previous reports showing the negative effects of different paradigms of prenatal stress on behavior outcomes [28][29][30][31]. It is interesting that the cluster analysis used to identify vulnerable and resilient animals revealed that the tests related to anxiety and sociability had higher predictive importance than the depressive one.…”
Section: Discussionsupporting
confidence: 91%